Gambaran Kompetensi Pendidik dalam Pengelolaan Pembelajaran Ekonomi di Era Pandemi Covid-19 - Anindita Trinura Novitasari; Ruski Ruski; Ika Lis Mariatun (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2021)
This research is conducted to understand the pedagogical techniques used in the learning of economics in STKIP PGRI Bangkalan. It applies quantitative descriptive method to recognize the percentage of respondents’ responses to each learning pedagogical variable indicator. This research found that during pandemic the learning pedagogy implemented by each lecturer of economics education program is categorized as very good. This is indicated by the percentage each indicator gained. The learning patterns of virtual classes have been in compliance with pedagogical techniques where students are given freedom to seek and get insights through guidance, direction and assistance the lecturers have provided. They function as motivator, facilitator and advisor in order to make students’ more confident to take decisions in understanding the materials given during the interactive virtual class. These pedagogical techniques have given students chances to understand cognitive, affective and psychomotor aspects simultaneously so that the learning becomes more effective.